2020
DOI: 10.1097/cej.0000000000000637
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of malignancy for solitary pulmonary nodules based on imaging, clinical characteristics and tumor marker levels

Abstract: Objective To establish a prediction model of malignancy for solitary pulmonary nodules (SPNs) on the basis of imaging, clinical characteristics and tumor marker levels. Methods Totally, 341 cases of SPNs were enrolled in this retrospective study, in which 70% were selected as the training group ( n = 238) and the rest 30% as the verification group ( n = 103). The imaging, clinical characteristics and tumor marker lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…After the screening of the titles and abstracts, the full text of 192 records were assessed for eligibility. Eventually, 32 studies were included in the systematic review 16,20–50 . The literature selection process was presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the screening of the titles and abstracts, the full text of 192 records were assessed for eligibility. Eventually, 32 studies were included in the systematic review 16,20–50 . The literature selection process was presented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 23 studies analyzed age as a continuous variable, and found significant association between increased age and malignant SPNs (aOR = 1.06, 95% CI: 1.05–1.07, p < 0.001 , I 2 = 66.0%; Supplementary Figure S1). 16,20–24,26–28,31,34,38,40,41,44,46,48–50 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There are also some limitations that cannot be determined in this protocol, such as the pathological nature of pulmonary nodules but the observation of tumor markers and immune indicators, combined with the changes of nodule size and risk level, also reflect the curative effect of traditional Chinese medicine to a certain extent. At present, there is a consensus on that tumor markers can be used as one of the evaluation methods of differentiating benign and malignant lung nodules [30], and we should observe lung cancer for abnormally elevated or progressive tumor markers such as carcinoembryonic antigen (CEA), neuron specific enolase (NSE) [38][39][40][41]. The percentage of T cell subsets in peripheral blood is an index to judge the anti-tumor immunity of patients.…”
Section: Discussionmentioning
confidence: 99%